Biochemistry and Molecular Biology - Hoffmeister, Dirk (The Mycota, A Comprehensive Treatise on Fungi as Experimental Systems for Basic and Applied Research, 2016)
This new edition provides a comprehensive look at the molecular genetics and biochemical basis of fungal biology, covering important model organisms such as Aspergilli while also integrating advances made with zygomycetes and basidiomycetes. This book groups a total of 15 chapters authored by expert scholars in their respective fields into four sections. Five chapters cover various aspects of gene expression regulation. These range from regulation in organismal interactions between parasitic fungi and their host plant, heavy metal stress and global control of natural product genes to conidiation and regulation through RNA interference. Two chapters are dedicated to signal transduction, highlighting MAP-kinase-dependent signaling and heterotrimeric G-proteins. Fungal carbohydrates are the subject of the third section, which addresses both polymeric cell wall carbohydrates and trehalose as an important, low molecular weight carbohydrate. The fourth section emphasizes the metabolism of major elements (carbon, nitrogen, sulfur) and critical cellular pathways for primary and secondary products.